Molecular basis of flexible peptide recognition by an antibody. (6th February 2020) - Makabe, Koki
Abstract: Antibodies can recognize various types of antigens with high specificity and affinity and peptide is one of their major targets. Understanding an antibody's molecular recognition mechanism for peptide is important for developing clones with a higher specificity and affinity. Here, the author reviews recent progresses in flexible peptide recognition by an antibody using several biophysical techniques, including X-ray crystallography, molecular dynamics simulations and calorimetric measurements. A set of two reports highlight the importance of intramolecular hydrogen bonds that form in an unbound flexible state. Such intramolecular hydrogen bonds restrict the fluctuation of the peptide and reduce the conformational entropy, resulting in the destabilization of the unbound state and increasing the binding affinity by increasing the free energy change. These detailed analyses will aid in the antibody design in the future.